2004
DOI: 10.1007/s00428-004-1016-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients

Abstract: Prostate cancer is the most common cancer in men and second in the cancer-related frequency of mortality. Matrix metalloproteinases (MMPs) are involved in tumor invasion and metastasis in various malignancies. MMP-2 and MMP-9 are capable of digesting collagen type IV. Numerous studies have demonstrated an association between increased MMP-2 and -9 expression and tumor progression in various tumors. In this study, the expression and activities of MMP-2 and -9 were assessed in serum probes and tumor tissue from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
1
38
1
4
Order By: Relevance
“…As expected, all studies have reported an increase in the MMP-to-TIMP ratio in cancer samples and an association with unfavorable prognostic parameters (54,74,75). Regarding enzymatic activity, increased activity of MMP2, MMP7, and MMP9 proteins have been observed in hormone-related cancers and increased activity associated with a more aggressive phenotype (55,58,64,74,76), consistent with the hypothesized role of these enzymes in cancer progression and invasion.…”
Section: Mmp and Timp Expression In Other Hormonerelated Cancerssupporting
confidence: 76%
See 1 more Smart Citation
“…As expected, all studies have reported an increase in the MMP-to-TIMP ratio in cancer samples and an association with unfavorable prognostic parameters (54,74,75). Regarding enzymatic activity, increased activity of MMP2, MMP7, and MMP9 proteins have been observed in hormone-related cancers and increased activity associated with a more aggressive phenotype (55,58,64,74,76), consistent with the hypothesized role of these enzymes in cancer progression and invasion.…”
Section: Mmp and Timp Expression In Other Hormonerelated Cancerssupporting
confidence: 76%
“…However, expression studies done using immunohistochemistry and in situ hybridization on prostate cancer tissue have shown a decreasing gradient of MMP1 protein from normal adjacent prostate, prostate intraepithelial neoplasia, to prostate cancer tissue (52). Similarly, down-regulation of MMP2 mRNA was observed in prostate cancer compared with normal tissue in two studies (53,54), whereas increased expression of MMP2 protein has been reported in five studies (55)(56)(57)(58)(59). This suggests a discrepancy between MMP2 RNA and protein levels in prostate tumors.…”
Section: Mmp and Timp Expression In Other Hormonerelated Cancersmentioning
confidence: 88%
“…Among different MMPs, MMP-2 and MMP-9, called gelatinases, disrupt the basement membrane by cleaving type IV collagen. Many studies have shown that increased levels of MMP-2 or MMP-9 in the serum or tissue samples of prostate cancer patients are correlated with advanced stage (19)(20)(21)(22)(23)(24)(25)(26). Whereas MMP expression is regulated by growth factors and cytokines, as well as oncogenes (27)(28)(29), regulation of MMP-2 or MMP-9 activities by AR signaling in prostate cancer cells is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were supported by a most recent independent report. 23 These parameters may be useful as a prognostic marker for human prostate cancer. Normalized Uzz its MMP-2 Figure 5 Relative activity of MMP-2 and -9 in serum samples.…”
Section: Discussionmentioning
confidence: 99%